2001
DOI: 10.1002/1521-3773(20010903)40:17<3155::aid-anie3155>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Two Mechanisms of Slow Host-Guest Complexation between Cucurbit[6]uril and Cyclohexylmethylamine: pH-Responsive Supramolecular Kinetics

Abstract: 20 times more rapid is the complexation of the organic ammonium ion receptor cucurbit[6]uril (CB6) with cyclohexylmethylamine than with the cyclohexylmethylammonium species (see scheme). Within the narrow pH region around the pKa value of the amine, the complexation kinetics are accelerated but the binding constant remains essentially unaffected. In this region, the ammonium complex is formed through binding of the amine form followed by fast protonation and not through direct complexation of the ammonium form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(85 citation statements)
references
References 47 publications
7
78
0
Order By: Relevance
“…6163 In contrast, the dataset generated for the HYDROPHOBE challenge was measured in the absence of added metal ions (solely 3 mM HCl to maintain constant pH, conditions which do not affect binding of neutral guests to cucurbiturils). 68 The employed hydrocarbons also covered a homologous series with a wide range of guest size and hydrophobicity, and the hydration free energies of these common guests are known. As will be seen, the cross-check of the hydration thermodynamics proved essential to introduce a reference-state correction.…”
Section: Introductionmentioning
confidence: 99%
“…6163 In contrast, the dataset generated for the HYDROPHOBE challenge was measured in the absence of added metal ions (solely 3 mM HCl to maintain constant pH, conditions which do not affect binding of neutral guests to cucurbiturils). 68 The employed hydrocarbons also covered a homologous series with a wide range of guest size and hydrophobicity, and the hydration free energies of these common guests are known. As will be seen, the cross-check of the hydration thermodynamics proved essential to introduce a reference-state correction.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Yu and coworkers found that the dissociation of neutral guests occurs in one step from CB7, but ammonium cyclohexyl derivatives egress in multi-step processes. 29 The hydrophobic, ion-dipole and hydrogen bonding interactions are the strongest in different guest positions in CB7.…”
mentioning
confidence: 99%
“…29 Nau and coworkers proposed on the basis of a comprehensive mechanistic study of the inclusion in CB6 that first an exclusion complex is produced by the coordination of the ammonium group to the negatively charged portal, and the organic moiety pivots into the cavity in a second step retaining the interaction with the macrocycle rim. 15 Such a flip-flop mechanism cannot take place with B + due to its bulkiness and the lack of a hydrogen bond donor site which could contribute to the stabilization of the exclusion complex. Moreover, its delocalized positive charge and hydrophobic character may render the exclusion complex formation energetically unfavorable.…”
mentioning
confidence: 99%
“…The most common ones are CB5, CB6, and CB7 (Scheme 3), of which only the last one is sufficiently large to encapsulate larger organic guests or residues with more than seven heavy atoms. We have studied the effects governing the thermodynamics and kinetics of host-guest complex formation of CB6 [25] and the influence of the CB7 cavity on the physical properties of the guest moieties [26]. Scheme 1. To explore new applications of the potentially most useful CB7, we have encapsulated as a fluorescent guest the azoalkane 2,3-diazabicyclo[2.2.2]oct-2-ene (DBO), a chromophore possessing a weak , absorption in the near UV ( nm in water) [26]- [31].…”
mentioning
confidence: 99%